EFEKTIVITAS BENTUK FISIK RANSUM DAN POD KAKAO (Theobrama cacao L.) YANG DIFERMENTASI DENGAN Aspergillus Niger TERHADAP KARKAS KELINCI REX LEPAS SAPIH - syahril bancin (Jurnal Peternakan Integratif, 2013)
ABSTRACT Feed is an important factor in the livestock business, balanced nutrition will result in higher carcass production. The objective of this study was to measure the effectiveness of Physical Form of Rations Containing Cocoa Pod  Fermentatied by Aspergillus niger on rabbit carcass. The experiment was conducted at the Compost Center Jl. Biotechnology University Of  Sumatera Utara. The study started from July to Sebtember 2012. Research method used randomized block design, treatment consisted of two factors: the physical properties of feed (mash and pellets) and fermented cocoa pod percentage (0%, 5%, and 10%) with two blocks. Parameters observed body weight, carcass, carcass percentage and comersial slice (foreleg, rack, hindleg). The results showed that there is no interaction (P>0,05) between physical feed and any levels cocoa pod fermentated. Physical feed and any levels cocoa pod fermentated even showed no significant different (P>0,05) for all variables. It can be concluded that fermented pod cocoa can be used as feed of Rex rabbit. Keywords: Carcass, Physical form rations, Pod cocoa,  fermentation, Aspergillus niger, Rex rabbit